2020
DOI: 10.3390/nu12082475
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Long-Term Aronia melanocarpa Extract Supplementation on Cognitive Performance, Mood, and Vascular Function: A Randomized Controlled Trial in Healthy, Middle-Aged Individuals

Abstract: Cognitive decline is associated with lifestyle-related factors such as overweight, blood pressure, and dietary composition. Studies have reported beneficial effects of dietary anthocyanins on cognition in older adults and children. However, the effect of anthocyanin-rich Aronia melanocarpa extract (AME) on cognition is unknown. Therefore, this study aimed to determine the effect of long-term supplementation with AME on cognitive performance, mood, and vascular function in healthy, middle-aged, overweight adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 69 publications
0
50
0
Order By: Relevance
“…Moreover, three studies reported effects on both cognitive performance and cardiometabolic risk markers, one on cognitive performance and vascular function, and seventeen studies on cardiometabolic risk markers and vascular function. Finally, we performed an intervention trial that addressed, for the first time, anthocyanin-induced effects on cognitive performance and underlying mechanisms (i.e., vascular function and cardiometabolic risk markers) [ 31 ]. With the exception of nine articles, the anthocyanin content of the intervention product was provided in all articles and ranged from 1.35–724 mg/day.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, three studies reported effects on both cognitive performance and cardiometabolic risk markers, one on cognitive performance and vascular function, and seventeen studies on cardiometabolic risk markers and vascular function. Finally, we performed an intervention trial that addressed, for the first time, anthocyanin-induced effects on cognitive performance and underlying mechanisms (i.e., vascular function and cardiometabolic risk markers) [ 31 ]. With the exception of nine articles, the anthocyanin content of the intervention product was provided in all articles and ranged from 1.35–724 mg/day.…”
Section: Resultsmentioning
confidence: 99%
“…Whyte et al [ 73 ] evaluated two dosages of a blueberry intervention and reported increased performance on the modified flanker test (MFT) after supplementation with the higher dose (254 mg anthocyanins). In an early study, our group evaluated the effect of two concentrations of a chokeberry extract and reported improved performance on the grooved pegboard test (GPT) after supplementation with the lower concentration (16 mg anthocyanins), but not with the higher concentration (27 mg anthocyanins) [ 31 ]. Scores on the five-choice reaction time task (FCRTT) were improved after supplementation with a blackcurrant juice in healthy young adults [ 71 ] but not with a blackcurrant extract in healthy older adults [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations